2019
DOI: 10.13005/bpj/1842
|View full text |Cite
|
Sign up to set email alerts
|

Anatomic Variation of Ct Scan in Chronic Rhinosinusitis Patients in Sanglah Provincial General Hospital

Abstract: The anatomical abnormalities of the nose and paranasal sinuses are the most common causes of rhinosinusitis. These anatomical variations can cause obstruction of the ostiomeatal complex (OMC) and interfere with the mucociliary clearance which allows the occurrence of chronic rhinosinusitis. Knowing the anatomic variations of the nose and paranasal sinuses in rhinosinusitis patients whose undergo operative procedure at Sanglah Provincial General Hospital is important because it can be used as a reference for pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…36 Moreover, Ratnawati 37 stated that septal deviation was the most common anatomical variation among 24 people (77%). 37 Aramani et al 38 also found that 40 people (74.1%) had a deviated septum and 18 people (33.3%) were chronic sinusitis patients. 39 Septal deviation is an anatomical variation that is often found and one of the predisposing factors for chronic sinusitis.…”
Section: Resultsmentioning
confidence: 95%
“…36 Moreover, Ratnawati 37 stated that septal deviation was the most common anatomical variation among 24 people (77%). 37 Aramani et al 38 also found that 40 people (74.1%) had a deviated septum and 18 people (33.3%) were chronic sinusitis patients. 39 Septal deviation is an anatomical variation that is often found and one of the predisposing factors for chronic sinusitis.…”
Section: Resultsmentioning
confidence: 95%
“…A total of 56 studies with 11 805 persons were included. All studies 13–66 involved a single population except for two studies 5,67 which recruited two distinct populations in each study. The studies were from 27 countries which can be divided into seven regions specifically Africa, Asia, Australia‐New Zealand‐Oceania, North America, South America, Europe and Middle East.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the results of the study, it was found that the most anatomical variations were concha hypertrophy in as many as 26 people. Another study showed that the most common anatomical variation was septal deviation [8], [9], [17], [18]. In Shresta's study, 68 patients (89.5%) had at least one type of anatomic variation while eight (10.5%) had no variation [13].…”
Section: Discussionmentioning
confidence: 99%